Biofertilizer and biocontrol properties of Stenotrophomonas maltophilia BCM emphasize its potential application for sustainable agriculture - Sharma, Pinki; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Plant Science, 2024)
Microbial biofertilizers or biocontrol agents are potential sustainable approaches to overcome the limitations of conventional agricultural practice. However, the limited catalogue of microbial candidates for diversified crops creates hurdles in successfully implementing sustainable agriculture for increasing global/local populations. The present study aimed to explore the wheat rhizosphere microbiota for microbial strains with a biofertilizer and biocontrol potential. Using a microbial culturing-based approach, twelve unique microbial isolates were identified and screened for biofertilizer/biocontrol potential using genomics and physiological experimentations.Molecular, physiological, and phylogenetic characterization identified Stenotrophomonas maltophilia BCM as a potential microbial candidate for sustainable agriculture. Stenotrophomonas maltophilia BCM was identified as a coccus-shaped gram-negative microbe having optimal growth at 37°C in a partially alkaline environment (pH 8.0) with a proliferation time of ~67 minutes. The stress response physiology of Stenotrophomonas maltophilia BCM indicates its successful survival in dynamic environmental conditions. It significantly increased (P <0.05) the wheat seed germination percentage in the presence of phytopathogens and saline conditions. Genomic characterization decoded the presence of genes involved in plant growth promotion, nutrient assimilation, and antimicrobial activity. Experimental evidence also correlates with genomic insights to explain the potential of Stenotrophomonas maltophilia BCM as a potential biofertilizer and biocontrol agent. With these properties, Stenotrophomonas maltophilia BCM could sustainably promote wheat production to ensure food security for the increasing population, especially in native wheat-consuming areas.